Review the Optimization of the Free Learning Curriculum - Ihda Husnul Khotimah; Betty Mauli Rosa Bustam; Pafi Rahmatullah Al Gifari (At-Taqaddum, 2022)
The emergence of a new curriculum, namely the independent curriculum as a breakthrough that requires time for educators and students to adjust, is the background of this research. Educators are beset by a lack of understanding regarding the concept of independent learning and how to make it happen in the learning process. Therefore, in its application, educators are required to be alert to the independent curriculum and always develop their own competence. In terms of developing the competence of educators, it refers to the four basic competencies that must be possessed and mastered. This article aims to examine more deeply the concept of independent learning and the important role of educators in it. This research uses the method of library research (library research) through a descriptive qualitative approach. Data sources were obtained from various references in the form of relevant journals, books, proceedings and articles. The results of the study show that teachers should own and master the four basic competencies according to Law Number 14 of 2005 article 10 paragraph 1 concerning teachers and lecturers. This is to support the concept of independent learning in which teachers are at the forefront and driving forces of national education. The results of the research can add to scientific treasures and have implications especially for educators and lecturers to maximize self-competence so that it is as quality as possible.